Answer:
1. 21
2. 896
3. 20.9
Step-by-step explanation:
Use BODMAS/BIDMAS to solve.
1−w−w2=64
Step 1: Simplify both sides of the equation.
−w2−w+1=64
Step 2: Subtract 64 from both sides.
−w2−w+1−64=64−64
−w2−w−63=0
For this equation: a=-1, b=-1, c=-63
−1w2+−1w+−63=0
Step 3: Use quadratic formula with a=-1, b=-1, c=-63.
w=
−b±√b2−4ac
/2a
w=
−(−1)±√(−1)2−4(−1)(−63)
/2(−1)
w=
1±√−251/
−2
38. Is the answer. Go go go!
Answer:
hjgjhgjhghjg
Step-by-step explanation:
ghjjgjesw54t32r3yggtfucgkyoughrhhfgh
Answer:
x = 1
Step-by-step explanation:
plug y = 6 on to the equation y =x + 5
=> 6 = x +5
=> x = 1